Framework for minimising the impact of regional shocks on global food security using multi-objective ant colony optimisation. (September 2017) - Golding, Peter; Kapadia, Sam; Naylor, Stella; Schulz, Jonathan; Maier, Holger R.; Lall, Upmanu; van der Velde, Marijn
Abstract: A general framework for the identification of optimal strategies for mitigating the impact of regional shocks to the global food production network is introduced. The framework utilises multi-objective ant colony optimisation (ACO) as the optimisation engine and is applicable to production-, demand-, storage- and distribution-focussed mitigation options. A detailed formulation for using trade as the mitigation option is presented and applied to a shock to wheat production in North America for illustrative purposes. Different strategies for improving the performance of the ACO algorithm are also presented and tested. Results indicate that the proposed framework has the potential to identify a range of practical trade mitigation strategies for consideration by decision makers, including trade-offs between the extent to which regional shocks can be mitigated and the degree to which existing trade arrangements have to be modified, as well as the relative importance of various trade agreements and different exporting countries. Highlights: Framework for mitigating impact of regional shocks to global food production. Use of multi-objective ant colony optimisation (ACO). Detailed formulation for considering trade as the mitigation strategy. Application to regional shock to wheat production in North America. Investigation of impact of different mechanisms for improving ACO performance.